The tadpole of Chaunus dorbignyi (Duméril & Bibron) (Anura, Bufonidae) - Borteiro, Claudio; Kolenc, Francisco; Tedros, Marcelo; Prigioni, Carlos (Zootaxa, 2006)
Chaunus dorbignyi and Chaunus fernandezae are the southernmost taxa of the Chaunus granulosus species group (formerly Bufo granulosus group). The biology of these species has been scarcely studied. In this sense, larval external morphology of Chaunus dorbignyi is described for the first time and compared with other species of the granulosus group, particularly with C. fernandezae. The tadpoles of C. dorbignyi at stages 31–35 are about 15 mm, and belong to the benthic ecomorphological guild. They have a depressed body, a slightly truncated snout, and the spiracle is placed on the posterior third of the body. The tail axis is straight, the dorsal fin begins at tail-body junction and ends broadly rounded. The vent tube is medial, it starts at midline and opens usually to the right, but in some specimens it opens to the left. The oral disc has a single row of marginal papillae, large dorsal gap, medium-sized ventral gap, and labial tooth row formula 2(2)/2. A multivariate analysis of morphometric variables provided differentiation from tadpoles of C. fernandezae, based on interorbital, eye-nostril and fronto-nasal distances, body maximum height and width, and dorsal gap length. However, the general aspect of both species is quite similar, and comparable to the tadpole of a related species, Chaunus pygmaeus. Other known tadpoles of the granulosus group are those of Chaunus granulosus beebei and Chaunus granulosus major, which differ from the above mentioned species in having a more depressed snout and body, and labial tooth row formula 2(2)/3. The observed variability in the vent tube opening of C. dorbignyi (and also in C. fernandezae) seems to depend on how the beginning of the ventral fin is folded, which is attached to the tube. This fact may have lead to different interpretations of vent tube configuration in the granulosus group, and must be taken into account in between-species comparisons.